Epigallocatechin Gallate (EGCG) Promotes the Immune Function of Ileum in High Fat Diet Fed Mice by Regulating Gut Microbiome Profiling and Immunoglobulin Production - Liu, Xiaoxia; Zhao, Ke; Jing, Nana; Kong, Qingjun; Yang, Xingbin (Frontiers in Nutrition, 2021)
This study was aimed to investigate the regulatory effect of epigallocatechin gallate (EGCG) on composition of gut microbiome, transcriptomic profiling of ileum, and their interplay relation in high fat diet (HFD) - induced obese mice. Intragastric administration of EGCG to C57BL/6J mice for consecutive 14 weeks remarkably decreased HFD induced excessive fat deposit (p < 0.001), and increment of serum TG, TC, HDL-C (p < 0.05), as well as improved glucose tolerance (p < 0.001). EGCG shifted the gut microbiota mainly by elevating the relative abundance of Parasutterrlla, Bacteroides, and Akkermansia (p < 0.01), decreasing that of norank_f_Erysipelotrichaceae, unclassified_f_Ruminococcaceae, Anaerotruncus, Roseburia, norank_Lachnospiraceae, and Lachnospiraceae_UCG_006 (p < 0.01) at genus level. In addition, EGCG affected the transcriptomic profiling of ileum, and the differentially expressed (DE) genes after HFD or/and EGCG treatment were mostly enriched in the immune reaction of ileum, such as the GO term of “immune effector process” and “phagocytosis, recognition”. Furthermore, the KEGG category of “immune diseases”, “immune system”, and “infection diseases: bacterial” were commonly enriched by the DE genes of the two treatments. Among those DE genes, 16 immunoglobulins heavy chain variable region encoded genes (Ighvs) and other immunity-related genes, such as complement component 2 (C2), interferon-induced transmembrane protein 1 (Iftm1), polymeric immunoglobulin receptor (pigR), and alanyl aminopeptidase (Anpep) were highly correlated with the shifted microbes in the gut (p <0.05, and absolute r > 0.5). Overall, the results above suggested that EGCG ameliorated the HFD induced metabolic disorder mainly by regulating gut microbiome profiling and the immunoglobulin production of ileum, while the genes expressed in the ileum, especially Ighvs, C2, Iftm1, pigR, and Anpep might play important roles in coordinating the immunity of mice regarding the gut microbes and the host interactions.